2016
DOI: 10.1016/j.juro.2016.04.079
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Variants in SULT1E1 and Response to Abiraterone Acetate by Men with Metastatic Castration Refractory Prostate Cancer

Abstract: Single nucleotide polymorphisms in SULT1E1 were significantly associated with time to treatment failure in men on abiraterone acetate therapy. The single nucleotide polymorphisms may serve as predictive markers for treatment with abiraterone acetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Other biological analytical approaches, such as those based on tumor immunohistochemistry, could bring more firmly established answers on that point. In complement to the herein-considered SNPs, mention must be given to the study by Agarwal et al [ 23 ], having shown a link between SNPs in the SULT 1 E 1 gene and time to treatment failure for prostate cancer patients under AA.…”
Section: Discussionmentioning
confidence: 99%
“…Other biological analytical approaches, such as those based on tumor immunohistochemistry, could bring more firmly established answers on that point. In complement to the herein-considered SNPs, mention must be given to the study by Agarwal et al [ 23 ], having shown a link between SNPs in the SULT 1 E 1 gene and time to treatment failure for prostate cancer patients under AA.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that diversity in gene expression and mutation among hormone-metabolizing enzyme genes, oncogenes, and suppressor genes and the difference in copy number variation and microsatellite instability could explain at least some of the racial disparities observed in survival. 27,28 Liu et al 29 found that Black and white patients had more prominent drug metabolism, cytotoxic therapy resistance, and endocrine therapy resistance than Asians. Prizment et al 30 demonstrated that the critical androgen-regulating gene HSD3B1 mutated differently among different races.…”
Section: Discussionmentioning
confidence: 99%
“…These may have contributed to the observed effects but were not evaluated in our study, which investigated germline factors for determining response to treatment. Furthermore, in a small study, germline variation in other signaling pathways such as the SULT1E1 variants described by Agarwal et al [ 36 ] has been shown to have effects on duration of response and warrant validation. The aforementioned factors will need to be evaluated in concert with our findings to gain a better understanding of the different factors affecting response to treatment.…”
Section: Discussionmentioning
confidence: 99%